Revisiting the genomic hypomethylation hypothesis of aging. Issue 1 (24th January 2018) - Unnikrishnan, Archana; Hadad, Niran; Masser, Dustin R.; Jackson, Jordan; Freeman, Willard M.; Richardson, Arlan
Abstract: The genomic hypomethylation hypothesis of aging proposes that an overall decrease in global DNA methylation occurs with age, and it has been argued that the decrease in global DNA methylation could be an important factor in aging, resulting in the relaxation of gene expression regulation and abnormal gene expression. Since it was initially observed that DNA methylation decreased with age in 1974, 16 articles have been published describing the effect of age on global DNA methylation in various tissues from rodents and humans. We critically reviewed the publications on the effect of age on DNA methylation and the expression of the enzymes involved in DNA methylation to evaluate the validity of the hypomethylation hypothesis of aging. On the basis of the current scientific literature, we conclude that a decrease in the global methylation of the genome occurs in most if not all tissues/cells as an animal ages. However, age‐related changes in DNA methylation in specific regions or at specific sites in the genome occur even though the global DNA methylation does not change.